FEATURES OF URINE METABOLOMIC STUDIES IN CHILDREN - Agzamova, Шоира; Pulatova, Камола (International Journal of Scientific Pediatrics, 2025)
Metabolomics is an advanced scientific field involving the comprehensive analysis of metabolites in biological samples, providing valuable insights into biochemical processes, disease mechanisms, and treatment outcomes. In pediatric medicine, urine metabolomic studies have become a vital tool for understanding various metabolic disorders and their early detection. Urine serves as an ideal matrix for metabolic profiling due to its non-invasive collection method and the high concentration of metabolites reflecting the body’s metabolic state. This article discusses the unique aspects of metabolic urine studies, especially in children, emphasizing the significance of urinary biomarkers in disease diagnostics, early detection, and monitoring. The methodologies employed, challenges encountered, and the potential application of metabolomics in clinical pediatric practice are examined.